Improving nursing care in a children’s hospital in rural India - Leavy, Jane D; Janes, Julie; Erickson, Tiffani A; Folsom, Susan M; Koncinsky, Jordan B; Schoenhals, Sarah; Patel, Meghna; Fassl, Bernhard (Indian Journal of Child Health, 2016)
Background: Nursing care quality in developing countries is an ongoing challenge leading to poor patient outcomes. The objective of this study is to evaluate changes in nursing performance providing routine cares following a training program in children’s hospital in Mota Fofalia, Gujarat, India. Methods: The main outcome measure was the proportion of newborns with vital signs and weights obtained by nursing staff before and after a training program. The training program consisted of an in-service reinforced by hands-on management of patient care for 2 weeks. Following the training, the nurses were observed for 2 months. Results: Observation of 138 newborn encounters demonstrated a 29.7% improvement in vital sign monitoring and 88.4% in weight monitoring from the 0% baseline. Conclusion: We observed a moderate improvement in measuring vital signs and a substantial improvement in measuring weights in newborns with the training intervention. For further improvement, continued training, and follow-up is indicated.